Sustainability calling : an analysis of the sustainability initiatives of Globe Telecom, Inc. from 2011 to 2016 - Abelita, Katharina (2019)
As countries commit themselves to achieving a carbon-neutral society, companies are challenged to reduce their environmental impact. This study aims to analyse the sustainability initiatives of a Philippine-based telecommunications company—Globe Telecom, Inc.—from 2011 to 2016. Through qualitative research design, this study (1) describes the initiatives performed in terms of its What, Why, and How (using GOLDEN framework for coding), (2) differentiate the strategic initiatives and cosmetic initiatives (using selected definitions and principles), and (3) determine initiatives which tackle telecommunications-specific issues. Findings show that throughout the study period, an annual average of 98 initiatives were carried out by the company and were mostly in the form of Asset Modification, New Products, Training, Modification of Procedures, and Donation and Funding. These initiatives mostly tackle issues regarding Self Realisation, Health, Environment, and Wealth Distribution for the benefit of various stakeholders, majority of which are the general public. With regard to issues specific to telecommunications companies, the company tackled 10 of the 14 identified issues. All of the initiatives which tackled these issues were understood as Strategic since these were integrated into the daily operations of the company and/or reduce the company’s environmental footprint, among others. The results of this study allow the focal company’s top management to further analyse their past performance in CSR, identify their current standing, set benchmarks, and design a better CSR and business strategies. Likewise, other telecommunications companies can gain inspiration from the initiatives of Globe in formulating their own initiatives which tackle issues that they find vital to their business.